Persepsi tokoh masyarakat dan peternak terhadap kinerja penyuluh dalam meningkatkan usaha peternakan sapi potong di Kecamatan Sangkub Kabupaten Bolaang Mongondow Utara - Umar, H; Lainawa, J; Lenzun, G D; Warow, Z M (ZOOTEC, 2021)
PERCEPTION OF COMMUNITY LEADERS AND FARMERS TOWARDS THE PERFORMANCE OF EXTENSION WORKERS IN IMPROVING BEEF CATTLE FARMING BUSINESS IN SANGKUB DISTRICT  NORTH BOLAANG MONGONSOW This research was a descriptive research that is aim to know  the perception of community leaders and breeders on the performance of extension workers. The selection of sample respondents was determined deliberately (Purposive) namely village officials, community leaders and farmers in the villages of Sangkub 1, Tombolango, Busisingo, Pangkusa and Sidodadi, as many as 30 respondents. Variable measurement is done by following the guidelines "Likert Scale" with member score on each respondent's answer. The results showed that the perception of community leaders on the performance of extension workers in improving the business of beef cattle farming in Sangkub District, North Bolmong Regency, in the extension aspect as a communicator 100% of respondents rated it useful, the material aspect of counseling 93% of respondents rated it useful and 7% of respondents were hesitant, aspects of counseling methods 63% of respondents rated it useful and 37% of respondents rated it as doubtful, aspects of counseling aids 100% respondents considered it un useful , aspects of the counseling target 93% of respondents rated it useful and 3% of respondents were hesitant, the time and place aspects of counseling 100% of respondents rated it useful, as well as aspects of increasing the beef cattle farming business 100% of respondents rated the benefits. Based on the results of analysis of the relationship of perception of community leaders and breeders to the performance of extension workers in improving the business of beef cattle farming with the model "rank spearman"  showed that there was a significant correlation between the perception of community leaders and village officials to the performance of extension workers in improving the business of beef cattle.